PROFICIENCY OF ACADEMIC STAFF IN THE UTILIZATION OF DIGITAL TECHNOLOGIES FOR TEACHING AND RESEARCH DEVELOPMENT IN NIGERIAN UNIVERSITIES (UNIZIK Journal of Educational Management and Policy, 2024)
The inability of many academic staff of the Nigerian universities in Anambra State to efficiently and effectively utilize most of the digital technologies in teaching and research development for attainment of educational goals and objectives, was the main essence for this study. The study however examined the proficiency of academic staff in utilization of digital technologies for teaching and research development in the Nigerian universities. Two research questions guided the study and two null hypotheses formulated for the study. The study employed the descriptive survey research design. Population of the study comprised 2,397 academic staff of two universities in Anambra State; that is, 1,867 and 530 academic staff from Nnamdi Azikiwe University (NAU) and Chukwuemeka Odumegwu Ojukwu University (COOU) respectively. Sample size of this study constituted a total of 479 academic staff selected at 20% using the stratified random sampling technique. A 24-item questionnaire titled: “Proficiency of Academic Staff in Utilization of Digital Technologies in Teaching and Research Development Questionnaire (PASUDTTRDQ)” was used for data collection. Validity of the questionnaire was determined by three experts. The coefficient value obtained for reliability is 0.86; while the hypotheses were tested using t-test statistics at an alpha level of 0.05 significance. The finding included among others that academic staff were not proficient in utilization of digital technologies for teaching and research development in the Nigerian universities in Anambra State. As such no significant differences in their mean score ratings on the extent of academic staff proficiency in utilization of digital technologies for teaching and research development in the Nigerian universities in Anambra State. The study recommended among others that the various governments (Federal & State) should support the university through adequate funding which will enhance sufficient provision of these digital technologies for improving academic staff proficiency in utilizing them for teaching and learning in the universities in Anambra State. Also, constant training and retraining programmes on the use of digital technologies in the universities should be sponsored by the university management, National Universities Commission (NUC) and other non-governmental organizations (NGOs) to improve academic staff proficiency in utilizing these digital technologies for teaching and learning in the universities in Anambra State
Keywords: Proficiency, Academic, Staff, Utilization, Digital, Technologies, Teaching, Research, Development, Universities